2018
DOI: 10.3847/1538-4357/aaa70d
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interaction between Magnetic Rossby Waves and Tachocline Differential Rotation in Producing Solar Seasons

Abstract: We present a nonlinear magnetohydrodynamic shallow-water model for the solar tachocline (MHD-SWT) that generates quasi-periodic tachocline nonlinear oscillations (TNOs) that can be identified with the recently discovered solar "seasons." We discuss the properties of the hydrodynamic and magnetohydrodynamic Rossby waves that interact with the differential rotation and toroidal fields to sustain these oscillations, which occur due to back-and-forth energy exchanges among potential, kinetic, and magnetic energies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 67 publications
1
70
1
Order By: Relevance
“…The periodicity of the bursts is a function of differential rotation amplitude as well as the effective gravity. Figure of Dikpati, McIntosh, et al () shows a more complex case of TNO, for which the period evolves with time, making the TNO more quasi‐periodic.…”
Section: Models For Hd and Mhd Rossby Waves In The Sunmentioning
confidence: 99%
See 1 more Smart Citation
“…The periodicity of the bursts is a function of differential rotation amplitude as well as the effective gravity. Figure of Dikpati, McIntosh, et al () shows a more complex case of TNO, for which the period evolves with time, making the TNO more quasi‐periodic.…”
Section: Models For Hd and Mhd Rossby Waves In The Sunmentioning
confidence: 99%
“…The result is a westward moving wave pattern as shown by the relative positions of the heavy black wave. The whole figure is modified from Figure in Dikpati, McIntosh, et al ().…”
Section: Concept Of Rossby Wavesmentioning
confidence: 99%
“…There are several physical mechanisms proposed that could cause the observed QBOs; flip-flop cycles, which is defined as the 180 • shift of the active longitudes with largest active regions (Berdyugina & Usoskin 2003), spatiotemporal fragmentation from differences in temporal variations in the radial profile Article number, page 1 of 13 arXiv:1904.03724v1 [astro-ph.SR] 7 Apr 2019 A&A proofs: manuscript no. Printer of the rotation rates (Simoniello et al 2013), instability of magnetic Rossby waves in the tachocline (Zaqarashvili et al 2010), and tachocline nonlinear oscillations, where periodically varying energy exchange takes place between the Rossby waves and differential rotation and the present toroidal field (Dikpati et al 2018). Additionally, a secondary dynamo working in the subsurface layers as the mechanism behind the QBOs is also proposed (Benevolenskaya 1998;Fletcher et al 2010), as the helioseismic observations revealed a subsurface rotational shear layer extending to a depth of 5% of the solar surface (Schou et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical models of Rossby waves can take several forms, from purely linear eigenvalue models for finding frequencies of propagation (Rieger et al 1984;Wolff 1992;Oliver et al 1998;Schecter et al 2001;Ballester et al 2002Ballester et al , 2004Zaqarashvili et al 2007Zaqarashvili et al , 2009Zaqarashvili et al , 2010aZaqarashvili et al , 2010bZaqarashvili et al , 2015Dimitropoulou et al 2008;Balk 2014;Raphaldini & Raupp 2015;Gurgenashvili et al 2017;Klimachkov & Petrosyan 2017a, 2017bLondon 2017;Zaqarashvili 2018) and growth rates of unstable modes (Gilman & Fox 1997;Dikpati & Gilman 1999, 2001bGilman 2000;Gilman & Dikpati 2000Cally 2003;Cally et al 2003Cally et al , 2008Dikpati et al 2003;Arlt et al 2005;Gilman 2015Gilman , 2017 to fully nonlinear models that generate both phase propagation and amplitude oscillations (Dikpati 2012;Balk 2014;Raphaldini & Raupp 2015;Dikpati et al 2018). Global models for convection, differential rotation, and magnetic fields can also show some Rossby wave propagation characteristics even for the convection zone, even though such systems generally do not produce Rossby waves per se.…”
Section: Introductionmentioning
confidence: 99%